Old Drug, New Pain. Roles and Challenges of Methadone Therapy in Pediatric Palliative Care: A Systematic Review - Benedetti, Francesca; Zoletto, Silvia; Salerno, Annalisa; Avagnina, Irene; Benini, Franca (Frontiers in Pediatrics, 2022)
Background Pediatric palliative care (PPC) is defined as the prevention and relief from suffering of families and children with life-limiting (LLDs) or life-threatening diseases (LTDs). These patients often experience pain, with morphine being the most widely used drug to treat it. Few studies investigated the role of methadone in PPC patients, although it is considered among the most effective and underutilized drugs in PPC. Objectives Our aim was to evaluate the efficacy, safety, and dosage of methadone in PPC. Methods Between August and October 2021 PubMed, Scopus and the Cochrane Library were searched for studies on the use of methadone in children with LLDs and LTDs. Articles were included if they met the following criteria: published in the last 10 years, English language, patients aged 0–23 years; children enrolled in a PPC center or receiving declared support from a PPC service; reporting of specific data on methadone in interventional trials, observational studies, or case series on >10 patients. The reporting of the article was guided by the PRISMA guidelines, and a critical appraisal of the included studies was performed using the JBI-tool. Results After duplicates removal and full-text assessment, four studies were included and another one was added after checking the references of the retrieved papers. All were retrospective, and the literature is concordant in documenting the lack of evidence. A total of 116 children received methadone in PPC. From our review emerges the poor quality of data collection: in only one study pain was assessed with standardized scales. All studies documented the effectiveness of methadone in treating complex pain, either nociceptive or neuropathic. No serious adverse events were reported, with no cases of cardiac arrhythmias. Conclusion Our results suggest that methadone could represent a suitable strategy for treating pain in PPC. However, the evidence base is insufficient, and further research is warranted.